First record of Leptoglossus occidentalis (Heteroptera: Coreidae) in Greece - Petrakis, P. V. (ENTOMOLOGIA HELLENICA, 2011)
The Nearctic coreid Leptoglossus occidentalis Heidemann 1910 (Hemiptera: Coreidae) known as the Western Conifer Seed Bug, is recorded for the first time in Greece. This highly dispersible species is well established in Europe and was collected by the authors in various areas of continental Greece (Central Evia, Attica and North Peloponnisos), suggesting a wide distribution in this country.